Polymorphonuclear-Mononuclear Ratio in Peripheral Blood as Hematologic Malignancy Predictor in Pancytopenia - JB. Suparyatmo; Dian Ariningrum; Indah Meyliza (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Pancytopenia is a laboratory finding of decreased hematological cells characterized by hemoglobin of <13.5 g/dL for males or <11.5 g/dL for females, leukocytes of <4x109/L and platelets of <150x109/L. The data from Dr. Moewardi Hospital reported 56 cases of pancytopenia in 2020. Follow-up tests such as reticulocyte test, Bone Marrow Puncture (BMP), or bone marrow biopsy are needed to determine the cause of pancytopenia. This study aimed to assess the performance of the Pm/M ratio of peripheral blood as a screening instrument to predict the cause of pancytopenia. A cross-sectional study was carried out on pancytopenia patients undergoing laboratory tests at the Clinical Pathology Laboratories of Dr. Moewardi Hospital from January 2020 to June 2021. The cut-off point of the Pm/M ratio was determined by ROC and AUC curves. The results were presented in a 2x2 table. The Pm/M ratio <0.91 as a predictor of hematological malignancy had a sensitivity of 82.9%, specificity of 82.9%, PPV 82.9, NPV 82.9%, LR positive 4.833 and LR negative 0.207. The Pm/M ratio can be used as a screening biomarker to predict the cause of pancytopenia before performing BMP and to distinguish between hematological malignancy and non-hematological malignancy.